Metabolic clues to salubrious longevity in the brain of the longest‐lived rodent: the naked mole‐rat. (3rd June 2015) - Triplett, Judy C.; Swomley, Aaron; Kirk, Jessime; Lewis, Katilyn; Orr, Miranda; Rodriguez, Karl; Cai, Jian; Klein, Jon B.; Buffenstein, Rochelle; Butterfield, D. Allan
Abstract Naked mole‐rats (NMRs) are the oldest‐living rodent species. Living underground in a thermally stable ecological niche, NMRs have evolved certain exceptional traits, resulting in sustained health spans, negligible cognitive decline, and a pronounced resistance to age‐related disease. Uncovering insights into mechanisms underlying these extraordinary traits involved in successful aging may conceivably provide crucial clues to extend the human life span and health span. One of the most fundamental processes inside the cell is the production of ATP, which is an essential fuel in driving all other energy‐requiring cellular activities. Not surprisingly, a prominent hallmark in age‐related diseases, such as neurodegeneration and cancer, is the impairment and dysregulation of metabolic pathways. Using a two‐dimensional polyacrylamide gel electrophoresis proteomics approach, alterations in expression and phosphorylation levels of metabolic proteins in the brains of NMRs, aged 2–24 years, were evaluated in an age‐dependent manner. We identified 13 proteins with altered levels and/or phosphorylation states that play key roles in various metabolic pathways including glycolysis, β‐oxidation, the malate‐aspartate shuttle, the Tricarboxylic Acid Cycle (TCA) cycle, the electron transport chain, NADPH production, as well as the production of glutamate. New insights into potential pathways involved in metabolic aspects of successful aging have been obtained by the identification of key proteins through which the NMR brain responds and adapts to the aging process and how the NMR brain adapted to resist age‐related degeneration. This study examines the changes in the proteome and phosphoproteome in the brain of the naked mole‐rat aged 2–24 years. We identified 13 proteins (labeled in red) with altered expression and/or phosphorylation levels that are conceivably associated with sustained metabolic functions in the oldest NMRs that may promote a sustained health span and life span.